2022
DOI: 10.1021/acsapm.2c01407
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Capture with Metal-Functionalized Polyacrylonitrile Composite Beads Containing Ag0, Bi0, Cu0, or Sn0 Particles

Abstract: The capture of radioiodine from nuclear processes and the mitigation of environmental release are important topic areas of research. Some of the more commonly employed chemisorption-type iodine scavengers reported in the literature are based on metal-exchanged porous sorbents such as Ag-zeolites or metal-functionalized aerogels and xerogels. However, another option is to use zero-valent metals directly that have known high affinities for iodine gas [i.e., I2(g)]. In this study, fine metal particles of Ag0, Bi0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The iodine loading of AgX is m % I = 25% compared to AgZ with m % I ≈ 11%, and this result is roughly in agreement with the ratio of Ag in the initial sorbents. The iodine loading experiments from the current study and previous studies ,,, show that sorbents with higher Ag loading tend to exhibit higher iodine loadings, but this is all dependent on the Ag utilization, which can vary from sorbent to sorbent. In the context of maximizing the iodine loading, maximizing the ion exchange potential for Ag recycle and iodide elution using the process described herein, as well as the chemical and mechanical integrity of the passive scaffold (aluminosilicate frameworks in the case for zeolites), optimization of these parameters in a search for more efficient sorbents should be considered in future studies.…”
Section: Results and Discussionsupporting
confidence: 52%
“…The iodine loading of AgX is m % I = 25% compared to AgZ with m % I ≈ 11%, and this result is roughly in agreement with the ratio of Ag in the initial sorbents. The iodine loading experiments from the current study and previous studies ,,, show that sorbents with higher Ag loading tend to exhibit higher iodine loadings, but this is all dependent on the Ag utilization, which can vary from sorbent to sorbent. In the context of maximizing the iodine loading, maximizing the ion exchange potential for Ag recycle and iodide elution using the process described herein, as well as the chemical and mechanical integrity of the passive scaffold (aluminosilicate frameworks in the case for zeolites), optimization of these parameters in a search for more efficient sorbents should be considered in future studies.…”
Section: Results and Discussionsupporting
confidence: 52%
“…In this study, several MS x -PAN composites were produced using a previously reported process 3,7,17,18 where MS x = Ag 2 S (75, 80, or 90 mass%), Bi 2 S 3 (80 mass%), or Cu 2 S (80 mass%). For each batch of composite beads, the general process was the same and all were prepared separately in glass beakers.…”
mentioning
confidence: 99%
“…After conversion to Bi@Al/SiO 2(4 mL) -2, its PXRD curve corresponds to the PDF card of Bi 0 , indicating the successful transformation from Bi 2 O 3 to Bi 0 . [40][41][42] In addition, no other phase is found, suggesting the amorphous composition of the Al-doped silica shell. In order to compare the role of aluminum in the iodine sorption process, all silicon sample named Bi@Al/SiO 2(4 mL) -∞ was prepared, and its PXRD pattern showed the same characteristics.…”
Section: Resultsmentioning
confidence: 99%